Pengaruh Gaya Kepemimpinan Demokratis Dan Etos Kerja Terhadap Kinerja Guru Pada Sekolah Yayasan Nurul A’la - Duri Noor Magnum; Barin Barlian; Ai Kusmiati Asyiah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine simultaneously and partially the Democratic Leadership Style which is influenced by the Work Ethic and Teacher Performance at the Nurul A'la Foundation School, Tasikmalaya City. The method used in this research is a quantitative method. The sample used amounted to 49 respondents. The data obtained are primary data through questionnaires. The analysis used is multiple linear regression analysis through SPSS Version 25. The results of this study indicate that democratic leadership style and work ethic simultaneously have a significant effect on teacher performance. Leadership style partially has no significant effect on teacher performance, work ethic partially has a significant effect on teacher performance at the Nurul A'la Foundation school, Tasikmalaya City